Effect of Cognitive Distortion On Social Media AddictionAmong College Students - Rima Nurdini; Dewang Sulistiana; Gian Sugiana Sugara (POTENSI : Journal of Education and Human Development, 2025)
This study aimed to describe the general picture of cognitive distortion and social media addiction among university students, as well as to identify the influence of cognitive distortion and social media addiction on social media addiction. The study employed a quantitative approach with a causal-comparative design and involved 184 university students as samples through probability sampling. The results showed that the majority of students were in the low category of cognitive distortion, while social media addiction was mostly in the moderate category. There was a strong positive correlation between cognitive distortion and social media addiction with a correlation coefficient of r = 0.387 and a contribution of 15% (R² = 0.150), as well as a significance value of 0.000, with 85% of other variables not explained in this study.